Eccrine Angiomatous Hamartoma - Jayaraman M; Janaki V R; Yesudian Patrick (Wolters Kluwer Medknow Publications, 1995)
Bier (1895) first reported the sudoriparous angioma as association of angioma and supralesional sweating with pain1. There have been several reports of this distinctive nevus1-4. We report one such case with a slight different morphology.